Kehamilan dengan Epilepsi - Teuku Yudhi Iqbal; Ariq Murfid (JURNAL RISET RUMPUN ILMU KESEHATAN, 2025)
Epilepsy is one of the most common chronic neurological disorders and can affect women of reproductive age, including during pregnancy. Pregnancy in women with epilepsy (WWE) presents various clinical challenges due to the complex interaction between physiological changes in pregnancy, fluctuations in antiepileptic drug (AED) levels, and the increased risk of seizures. Seizures during pregnancy not only pose a threat to maternal safety but also carry potential complications for the fetus, such as hypoxia, trauma, and impaired uteroplacental blood flow. Therefore, the management of epilepsy during pregnancy requires a careful and comprehensive approach. This report presents the case of a 41-year-old woman, G4P2A1, at 37–38 weeks of gestation, who presented to the emergency obstetric unit at Cut Meutia General Hospital with complaints of contractions following three episodes of seizures within the previous 24 hours. The patient had a 16-year history of epilepsy and was on regular neurologist follow-up, but she had discontinued her AEDs three weeks prior due to medication unavailability. She underwent an elective cesarean section with concurrent fimbriectomy as a permanent contraceptive method. Postoperatively, the patient experienced status epilepticus and decreased consciousness for approximately 24 hours. A multidisciplinary approach involving neurologists was implemented, including AED administration, enteral nutrition, close monitoring of vital signs and urine output. The patient's condition gradually improved, and she was discharged on the seventh day in a stable condition with well-healed surgical wounds. This case highlights the importance of optimal seizure control during pregnancy. Preconception counseling, appropriate AED selection, and regular drug level monitoring are essential in minimizing maternal and fetal complications. A multidisciplinary collaboration between obstetricians and neurologists plays a crucial role in achieving favorable outcomes.